A Decision Support System on Employee Assessment Using Analytical Network Process (ANP) and BARS Methods - I Made Dwi Putra Asana; I Gede Iwan Sudipa; Kadek Ari Prayoga Putra (Institute of Computer Science (IOCS), 2021)
Employee assessment is needed in evaluating performance and granting rewards to employees. PT. Kupu-Kupu Taman Lestari conducts an employee performance appraisal using Microsoft Excel. The growth of employee data and assessment variables resulted in the calculation method that was carried out could not provide employee ranking information quickly. The application of Microsoft Excel in processing employee valuation data has weaknesses in data documentation. The purpose of this study is the company has a website-based decision support system that makes it easy for companies to get employee performance appraisal information. The employee performance data ranking method used is the Analytical Network Process (ANP) and the performance evaluation criteria are prepared based on the Behaviorally Anchor Rating Scale (BARS) approach. BARS is used in determining criteria along with a scale of behavior that represents the performance of each criterion. ANP is used to process data of importance between criteria so that it can produce criteria weights based on a comparison between criteria. The results of this study are website-based decision support systems that can be accessed by company management via a web browser. System testing is built based on testing manual calculations with the system and testing the user's system according to the McCall model. The system calculation test shows that the system has produced the same calculation value as the manual calculation. System user testing shows that the system built meets user needs, displays information according to user input correctly, is safe from unauthorized parties, and the system is easy to use.